Additional Treatment Methods for Rheumatoid Arthritis Symptoms. Literature review - Gryboś , Kacper; Lewandowski, Mikołaj; Kwiatkowska, Zofia; Kurkiewicz, Wojciech; Woźniak, Oskar; Mikulska, Jowita; Wąsik, Joanna; Sepioło, Weronika; Kiełbratowska, Julia (Quality in Sport, 2025)
Rheumatoid arthritis (RA) is a chronic inflammatory disease that significantly impacts patients’ mobility and quality of life. While pharmacotherapy remains the primary approach to symptom management, increasing attention is being given to non-pharmacological treatment methods. This literature review explores alternative therapeutic interventions for RA, including anti-inflammatory diets, physical exercise, education, curcumin supplementation, psychotherapy, stem cell therapy, cannabinoids, cryotherapy, yoga, meditation, and mindfulness. These methods target different aspects of RA pathology, such as inflammation modulation, pain reduction, and psychological well-being. Studies suggest that dietary modifications, particularly the Mediterranean diet, may help reduce inflammation and improve joint function. Regular physical activity has demonstrated benefits in maintaining joint mobility and reducing pain perception. Psychological interventions, including cognitive-behavioral therapy, enhance patients’ coping mechanisms, reducing stress-related inflammation and depressive symptoms. Additionally, emerging treatments like stem cell therapy and cannabinoids offer promising but still experimental alternatives. While these interventions cannot replace pharmacotherapy, they can serve as valuable adjuncts, potentially improving clinical outcomes and reducing reliance on long-term medication. Further research is needed to establish standardized guidelines for integrating these approaches into RA management strategies. This review highlights the necessity of a comprehensive, multidisciplinary approach to RA treatment that includes both conventional and alternative therapies.